2021
DOI: 10.1002/nur.22121
|View full text |Cite
|
Sign up to set email alerts
|

Better nurse work environments associated with fewer readmissions and shorter length of stay among adults with ischemic stroke: A cross‐sectional analysis of United States hospitals

Abstract: Stroke is among the most common reasons for disability and death. Avoiding readmissions and long lengths of stay among ischemic stroke patients has benefits for patients and health care systems alike. Although reduced readmission rates among a variety of medical patients have been associated with better nurse work environments, it is unknown how the work environment might influence readmissions and length of stay for ischemic stroke patients. Using linked data sources, we conducted a cross-sectional analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…With each additional patient-per-nurse (ie, poorer nurse staffing), odds of 30-day readmission were 3 times higher for surgical patients with OUD (9%) compared with only 3% higher for the overall sample. Consistent with existing evidence, 40 , 41 each categorical improvement in the quality of the nurse work environment was associated with improvements in all measured outcomes, although the analysis did not detect a stronger effect of the nurse work environment on postsurgical outcomes for patients with OUD versus those without. Our findings that nursing resources positively impact outcomes for surgical patients with OUD is consistent with a large body of existing evidence on samples of patients including those with Alzheimer’s disease and serious mental illness.…”
Section: Discussionsupporting
confidence: 70%
“…With each additional patient-per-nurse (ie, poorer nurse staffing), odds of 30-day readmission were 3 times higher for surgical patients with OUD (9%) compared with only 3% higher for the overall sample. Consistent with existing evidence, 40 , 41 each categorical improvement in the quality of the nurse work environment was associated with improvements in all measured outcomes, although the analysis did not detect a stronger effect of the nurse work environment on postsurgical outcomes for patients with OUD versus those without. Our findings that nursing resources positively impact outcomes for surgical patients with OUD is consistent with a large body of existing evidence on samples of patients including those with Alzheimer’s disease and serious mental illness.…”
Section: Discussionsupporting
confidence: 70%
“…For example, several studies have reported that the unit work environment is associated with patient outcomes and with levels of nurse burnout. 33,34…”
Section: Introductionmentioning
confidence: 99%
“…Comprising the largest group of providers in hospitals, nurses have long been calling to improve their working conditions, including improving staffing and work environments to retain nurses and improve patient outcomes ( Brom, Brooks Carthon, Sloane, McHugh, & Aiken, 2021 ; Lasater et al, 2021 ). This has become more important now than ever ( Schlak, Aiken, Chittams, Poghosyan, & McHugh, 2021 ).…”
mentioning
confidence: 99%